Pengaruh E-commerce Shopee Terhadap Volume Penjualan pada Liga Store Makassar - Ahmad Kalamullah; Abdi Akbar; Ilham Wardhana Haeruddin; Anwar Ramli; Burhanuddin Burhanuddin (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
The purpose of this study is to find out the Influence of Shopee E-Commerce on Sales Volume in the Makassar League. This type of research is associative with a quantitative approach, in the Store League located on Jalan Yusuf Dg. Ngawing No. 9B, Tidung Village, Rappocini District, Makassar City. The research was conducted using a simple linear regression analysis technique. The object of this research is E-Commerce Shopee Liga Store Makassar. The data sources used are primary and secondary data. The data test techniques used as test tools in this study are validity test, realism, normalias test, simple linear regression analysis, partial test (T test), determination coefficient test. The sample used in this study is the customer dishopee of the Liga Store. The overall results of the study show that Shopee E-Commerce has a significant effect on Sales Volume in the Liga Store.